Assessment of Liver Steatosis and Fibrosis in Newly Diagnosed Acromegaly: An Integrated Approach Utilizing Quantitative Ultrasound, Histological Analysis and Biochemical Markers" - Saira Saleem, Mubasher Ahmad, Wajeeha Imran Andrabi, Fareeha Naseer Syed, Ayesha Kamran, Rukhsana Gulzar, Rida Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: Acromegaly, a disorder characterized by excessive growth hormone (GH) and insulin-like growth factor-1 (IGF-1) release, is associated with systemic consequences, including hepatic steatosis and fibrosis. Early identification of liver involvement is crucial for optimal therapy. Place of Study: Punjab Medical College, Faisalabad Medical University, Faisalabad Pakistan Study Duration: February 2021 until January 2023 Material and Methods: This study investigates the efficiency of quantitative ultrasonography (QUS) techniques and biochemical markers in detecting liver steatosis and fibrosis in newly diagnosed acromegaly patients. Fifty acromegaly patients and 30 healthy controls performed QUS imaging (shear wave elastography [SWE] and controlled attenuation parameter [CAP]) and serum biomarker analysis (FIB-4, APRI, and ELF scores). Liver biopsies were performed in a subgroup of patients for validation. Results: demonstrated substantial relationships between QUS parameters, biochemical markers, and histological findings. QUS revealed great sensitivity and specificity for detecting steatosis and fibrosis, while biochemical markers provided complementing diagnostic value. Conclusion: This work demonstrates the promise of non-invasive approaches for early liver screening in acromegaly, enabling timely intervention and improved outcomes. Keywords: Quantitative ultrasound (QUS), Controlled attenuation parameter (CAP), Biochemical markers, FIB-4 score, APRI score, ELF score, Liver biopsy